Dry-Ice Blasting of Auto Robotic Assemblies - Nazim Baluch; Shahimi Mohtar; Che Sobry Abdullah (International Journal of Supply Chain Management, 2016)
Welding robots are extensively applied in the automotive assemblies and Spot Welding is the most common welding application practiced in the auto stamping assembly manufacturing. Though adaptive resistance welding control automatically compensates to keep production and quality up to the levels needed as welding gun tips undergo wear so that the welds remain reliable; the system cannot compensate for deterioration caused by the slag and spatter on the part holding fixtures, sensors, and gun tips. To cleanse welding robots of slag and spatter, dry-ice blasting has proven to be an effective antidote. This paper describes Spot welding process, analyses the slag and spatter formation during robotic welding of stamping assemblies, and concludes that the dry ice blasting processs utility in cleansing of welding robots in auto stamping plant operations is preeminent.